Use of angiotensin converting enzyme inhibitors is associated with reduced risk of late bladder toxicity following radiotherapy for prostate cancer. (March 2022) - Kerns, Sarah L.; Amidon Morlang, Ashley; Lee, Sharon M.; Peterson, Derick R.; Marples, Brian; Zhang, Hong; Bylund, Kevin; Rosenzweig, Doug; Hall, William; De Ruyck, Kim; Rosenstein, Barry S.; Stock, Richard G.; et al.
Highlights: ACEi used during prostate cancer radiotherapy protected against late hematuria. The effect was independent of clinical factors associated with late hematuria. A polygenic risk score for blood pressure was not associated with late hematuria. Functional studies are needed to uncover the biologic basis of these findings. A randomized trial is needed to evaluate clinical impact. Abstract: Background and purpose: Genome-wide association studies (GWAS) of late hematuria following prostate cancer radiotherapy identified single nucleotide polymorphisms (SNPs) near AGT, encoding angiotensinogen. We tested the hypothesis that patients taking angiotensin converting enzyme inhibitors (ACEi) have a reduced risk of late hematuria. We additionally tested genetically-defined hypertension. Materials and methods: Prostate cancer patients undergoing potentially-curative radiotherapy were enrolled onto two multi-center observational studies, URWCI ( N = 256) and REQUITE ( N = 1, 437). Patients were assessed pre-radiotherapy and followed prospectively for development of toxicity for up to four years. The cumulative probability of hematuria was estimated by the Kaplan-Meier method. Multivariable grouped relative risk models assessed the effect of ACEi on time to hematuria adjusting for clinical factors and stratified by enrollment site. A polygenic risk score (PRS) for blood pressure was tested for association with hematuria in REQUITE and our Radiogenomics Consortium GWAS. Results: Patients taking ACEi during radiotherapy had a reduced risk of hematuria (HR 0.51, 95%CI 0.28 to 0.94, p = 0.030) after adjusting for prior transurethral prostate and/or bladder resection, heart disease, pelvic node radiotherapy, and bladder volume receiving 70 Gy, which are associated with hematuria. A blood pressure PRS was associated with hypertension (odds ratio per standard deviation 1.38, 95%CI 1.31 to 1.46, n = 5, 288, p < 0.001) but not hematuria (HR per standard deviation 0.96, 95%CI 0.87 to 1.06, n = 5, 126, p = 0.41). Conclusions: Our study is the first to show a radioprotective effect of ACEi on bladder in an international, multi-site study of patients receiving pelvic radiotherapy. Mechanistic studies are needed to understand how targeting the angiotensin pathway protects the bladder.